Energy and environmental performance of photovoltaic cooling using phase change materials under the Mediterranean climate. (15th February 2023) - Foteinis, Spyros; Savvakis, Nikolaos; Tsoutsos, Theocharis
Abstract: The energy and environmental performance of photovoltaic (PV) panel cooling, when using phase change materials (PCMs), was examined. Actual, long-term field data were collected from a PV and a PV-PCM system, both operating under Mediterranean conditions (Greece). The energy analysis revealed that even though cooling increases (9.4%) the panel's energy output, PCM cooling is associated with a high initial energy investment, leading to low energy-return-on-investment values (1.79) compared to PV (4.94). High energy payback times were observed for the PV-PCM (⁓14 years) compared to the PV system (⁓5 years). Furthermore, the life cycle assessment methodology revealed that PCM cooling increases PV's total environmental footprint by 21.9%. However, in the Greek context, the additional electricity attributed to PV cooling leads to significant environmental gains through fossil-fuel-dependent electricity substitution. Cooling can also decrease the rate of cell degradation and prolong PV useful life, leading to additional environmental gains. Due to PCM's initial high energy investment, other cooling technologies should also be examined since, apart from improving electricity output and stability, cooling can also reduce PV's impact on land use, increase the power sector's decarbonization, and address global warming's impact on PV performance by reducing temperature fluctuations and extremes on the panel's surface. Highlights: The environmental performance of a PV-PCM was examined in Mediterranean. PCM increases the total environmental footprint by ⁓22% compared to a standalone PV. Cooling from PCM increases electricity output also increases by 9.4%. Displaced electricity from the grid leads to large environmental gains. Results were sensitive to changes in PV's electrical efficiency and useful life.